Efektivitas Ivermectin dan Albendazole dalam Melawan Ostertagia pada Anakan Domba di Bogor, Indonesia - Silvia Puspitasari; Erni Sulistiawati; Muladno Basar; Achmad Farajallah (Institut Pertanian Bogor, 2015)
Giving a half-dose of an anthelmintic is a simple method for detecting resistance in parasites infesting small ruminants. When a single anthelmintic fails in native sheep from Indonesia, a combination of anthelmintics from different chemical classes with different mechanism of action is an alternative parasite-control strategy. This study compared the anthelmintic effectiveness of ivermectin (IVM) and albendazole (ABZ) have given either separately as a full-dose or half-dose or co-administered to sheep naturally infected with Ostertagia. Twelve sheep from Bogor, Indonesia were divided into six groups based on the anthelmintic treatment: half-dose IVM, full-dose IVM, half-dose ABZ, full-dose ABZ, combined (half-dose IVM + half-dose ABZ), and control groups. The treatment effectiveness was determined using the Faecal egg count reduction (FECR) on before and after 7, 14, 21, 28, 35, and 42 days of treatment. FECR of half-dose IVM, full-dose IVM, half-dose ABZ, full-dose ABZ, and both combined ranged from 78-100%, 96-100%, -71-89%, -521-64%, and 54-100%, respectively. The results showed that full-dose IVM was the most effective to against Ostertagia until 42 days and followed the combined that effective until 28 days. Half-dose and full-dose ABZ weren’t effective to against Ostertagia.